G69(P) A quality improvement project to improve paediatric diabetic services transition process. (May 2019) - Sadasivam, I; Riddle, M; Furness, L
Abstract : Objective: Our aim is to change the existing diabetes transition clinic model in a teaching hospital, which involves introduction of young patients to adult diabetes team in a routine joint outpatient clinic. Background: We initiated this multi disciplinary focused redesign of transition service as patient feedback from previous transition clinics showed reduced confidence in moving on to adult services and managing their diabetes. This transition clinic model meets all standards of YOU'RE WELCOME 2017 proposal 1 to improve adolescent health services. Methods: We developed a patient led transition clinic based on feedback given by patients over telephone interviews who transitioned over a period of four years about how they wanted the transition service to be delivered. Since June 2017, transition clinics are run once every 4 months. Patients ready for transition are invited to attend a small group transition session of 6 to 8 patients along with their parents or carers to meet the Paediatric and adult diabetes teams. They are given the choice to opt out and request routine outpatient appointment if they did not want to participate in group sessions. The transition session takes place in a patient friendly environment away from a clinic setting. Over a welcome speech patients are asked to identify the topics they would like to see discussed in the clinic. Parents or carers are advised to stay in adjacent room where they will meet professionals separately until the group discussions are finished and then invited back to join the patients. Recurring themes of discussion in patient groups include parental relationship, weight management, drinking alcohol, safe driving, managing diabetes during festivals or long journeys, intake of recreational drugs and tattoos. Results: Patient feedback post transformed clinics showed improved attendance rates, patient satisfaction and confidence in transitioning to adult services. Appropriate parent involvement, satisfaction with services and meeting the adult team before transfer are associated with improved transition outcomes. 2 References: YOU'RE WELCOME PILOT 2017 – refreshed standards for piloting. www.youngpeopleshealth.org.uk Colver, et al. A longitudinal, observational study of the features of transitional healthcare associated with better outcomes for young people with long-term conditions. BMC Medicine 2018;16:111.